Analisis Pola Pembelian Mobil di Indonesia Menggunakan Metode ID3 - Maria Yohana Gabriela Sasi; Yampi R Kaesmetan (Yayasan Literasi Sains Indonesia, 2025)
Indonesia's geographical conditions consisting of islands encourage the need to develop efficient transportation, especially automotive, to improve the country's economy. Cars are seen as safer vehicles than motorbikes, and with the increasing number of automotive companies, competition in the market is getting tighter. Car sales, especially from brands such as Toyota, Honda, and Mitsubishi, have shown rapid growth, with Toyota recording sales growth of 6.5% and Honda increasing by 56% in 2023. This condition requires companies to understand consumer needs and implement the right business strategies. The comfort and quality of the car are the main priorities in choosing a vehicle, although price is also an important consideration. With the growth of marketing through social media, the expected data can be used for further analysis, so that manufacturers can improve the quality of their products. The purpose of using the ID3 Method (Iterative Dichotomiser 3) as an algorithm to explore patterns in car purchasing decisions in Indonesia, given its ability to form decision trees that can reflect alternative choices and decision results. This study aims to analyze car purchase data and provide more insight into consumer preferences in the context of the Indonesian automotive market